2017
DOI: 10.1016/j.jaip.2016.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use in Early Life, Rural Residence, and Allergic Diseases in Argentinean Children

Abstract: Background Little is known about differential effects of antibiotic use on allergic diseases in rural versus urban environments. Objective: To examine whether area of residence in the first year of life modifies the relation between antibiotic use in early life and allergic diseases during childhood. Methods Cross-sectional study of allergic diseases in 1,517 children (ages 6–7 years) attending 101 schools in urban and rural areas of San Francisco (Córdoba, Argentina). Current asthma, wheeze, and allergic rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…It should be noted that much evidence suggested postnatal exposure to antibiotics might increase the risk of the development of allergic diseases in children. [10][11][12][13][14][15][16][17] For instance, Ahmadizar et al 10 found a positive association between early-life antibiotic exposure and the risk of developing symptoms such as eczema, hay fever, and food allergy later in life through meta-analyses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that much evidence suggested postnatal exposure to antibiotics might increase the risk of the development of allergic diseases in children. [10][11][12][13][14][15][16][17] For instance, Ahmadizar et al 10 found a positive association between early-life antibiotic exposure and the risk of developing symptoms such as eczema, hay fever, and food allergy later in life through meta-analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported that maternal antibiotic exposure during pregnancy was associated with an altered infant gut microbiome composition 8,9 which may lead to subsequent allergy diseases and obesity in childhood. It should be noted that much evidence suggested postnatal exposure to antibiotics might increase the risk of the development of allergic diseases in children 10‐17 . For instance, Ahmadizar et al 10 found a positive association between early‐life antibiotic exposure and the risk of developing symptoms such as eczema, hay fever, and food allergy later in life through meta‐analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that antibiotics in the first few years of life have been associated with increased risks of allergic disease in later childhood 14. Some studies have shown that exposure and use of antibiotics in infants may increase the risk of AR or asthma 5,6,15,16. Other studies have shown that there is a direct relationship between antibiotic use in the first 3 years of life and asthma and allergy symptoms in children aged 6–8 years old 17.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic exposure during maternal pregnancy or early life 67 68 69 70 71 and cesarean delivery 57 72 73 can increase the prevalence of asthma in children by affecting the gut microbiota and other mechanisms. Anti-parasitic therapy is also shown to be associated with increased prevalence of asthma.…”
Section: Environmental and Microbial Exposurementioning
confidence: 99%